CFD Simulation of the Wave Pattern Above a Submerged Wave Energy Converter - Hengrui Li; Jinming Wu (Journal of Marine Science and Engineering)
This work aims to establish a numerical model to investigate the wave interaction induced by the motion of a submerged cylindrical wave energy converter. The results show that when the submerged cylinder is in forced sinusoidal heave motion, distinct hollows and humps are produced on the free surface. As the heave amplitude increased from 1 m to 1.8 m, the depth of the hollow increased by 454%, and the height of the hump increased by 370%. Along with strong nonlinear phenomena, the generation of up to the fourth harmonic on the free surface above the submerged body is found, and the highest amplitude of the second harmonic waves reached 68% of the primary frequency. This indicates that the energy distribution of the wave is decomposed and rebalanced, and some energy in the primary frequency accumulates towards higher harmonics. When the submerged cylinder is in forced sinusoidal surge motion, the free surface elevation decreases in a stepwise manner as the wave transitions from crest to trough. As the cylinder pitches, the elevation of the wave trough decreases by 5% compared to when the submerged cylinder remains static.